Monitoring of Shallow-Grooved Tramway Crossings - Kreckova, Magdalena; Krejcirikova, Hana (Communications - Scientific Letters of the University of Zilina, 2023)
The article presents selected results and the sequencing of research into the project "Long-Term Monitoring of Rail Structures in Tramway Crossings with a Focus on Shallow-Grooved Crossings Aimed at the Optimization of their Maintenance and Noise Reduction", which was running with support from the Technology Agency of the Czech Republic within the Zeta Project (project registration No. TJ04000257) in 2020-2022. The project was elaborated jointly with the Prazska strojirna a.s. Company in cooperation with the Prague Public Transit Company (hereinafter PPTC). The project's objective was to optimize the maintenance of tramway tracks with a focus on shallow-grooved crossings in rail structures taking into account the noise emission levels during the life cycle of these crossings.
Keywords: rail structure; deep-grooved crossing; shallow-grooved crossing; wear; noise emission level